If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11s + -14 = 184 Reorder the terms: -14 + 11s = 184 Solving -14 + 11s = 184 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 11s = 184 + 14 Combine like terms: -14 + 14 = 0 0 + 11s = 184 + 14 11s = 184 + 14 Combine like terms: 184 + 14 = 198 11s = 198 Divide each side by '11'. s = 18 Simplifying s = 18
| (x-4)(x-4)=x+2 | | -3.6+3v=1.2 | | 8x+768=-642 | | 3(2)-4y=14 | | 2x^2-6x+21=0 | | 5(z-4)+6z-4= | | y^2-32= | | 6x+4x^2=5 | | A=rs+r | | 2x+4=122 | | y=3i | | 3D+8D=60 | | -6x-(9-x)-9= | | 10(z+4)-4(z+2)=3(z-1)+2(z-3) | | -7=8+x | | 5h+2(11-h)=(-5) | | -9+4y= | | r-8.3=-6.6 | | 4d-13+7d=(-24) | | 4z+2z=5z+5 | | 4x(x-6)=3(6-x) | | -5(z+7)=-4z-9 | | 6y+10-3y=9+2y-4 | | 7n-5=10+13 | | 8(x-6)-(4-9x)=16x | | 5x-5=10n+13 | | x^2-11x+5.25=0 | | 10x+7x=17x | | 2x+3y-100=0 | | 4x+27=3x+3y | | 7(x+8)+2(6x-7)=18(x+3)-5 | | 10x^2-34x+12=0 |